Tillering of Tifton 85 bermudagrass in response to nitrogen rates and time of application after cutting - Linda Monica Premazzi; Francisco Antonio Monteiro; José Eduardo Corrente (Scientia Agricola, 2003)
Nitrogen fertilization is determinant for pasture productivity, as it results in increasing forage yield and is associated with the growth physiology of forage plants. An experiment was carried out in a greenhouse to evaluate the effects of nitrogen rates and times of application after cutting on Tifton 85 Bermuda grass (Cynodon spp.) tillering. Plants were grown in a Typic Quartzipsamment soil and nitrogen rates were 0, 80, 160 and 240 mg kg-1 of soil; times of application were immediately after and seven days after cutting. A 4 x 2 factorial experiment was set in a completely randomized block design (n= 4). Plants were evaluated in two sequential growth periods - 39 and 41 days. Nitrogen rates affected tiller density, considering the initial number of tillers in the second growth and the emerged and final number of tillers at the end of the growth periods. Tiller weight increased up to the nitrogen rate of 201 and 185 mg kg-1 of soil in the first and second growth periods, and the correlation coefficients between the final number of tillers and dry matter yields in the top part of the plant for these periods were 0.92 and 0.94, respectively. The rate of tiller development, evaluated in each of the seven-day periods, was affected by nitrogen rates and time of application. There was an effect of rates and time of application in the first and a significant interaction between rates and time in the second growth period.